Noise identification based on spectral analysis and noisy transfer function approach for fuel cells - DURSUN, ERKAN; KILIÇ, OSMAN (DE GRUYTER POLAND SP Z O O, 2020)
In this study, some measurements like the current, voltage and hydrogen flow based on the fuel cell are investigated in spectral-domain as well as their time-domain representations and then, their spectral properties are extracted. Besides this, taking the simplified transfer function approach into account, which is defined between the hydrogen flow and current of the cell as an input-output pair, more detailed results are obtained. Therefore, the spectral parts of the fuel cell are put into categories under the impacts coming from the process, measurement circuits and digitizers. The process noise to be defined at very small frequencies (<15 Hz) can be explained as the effects of the various physical and chemical interactions emerging in the fuel cell. Moreover, this study analysed the spectral characteristics of fuel cells for current, voltage and hydrogen flow in detail.
Keywords: hydrogen energy; fuel cell; time-frequency analysis; spectral analysis; transfer function; noise; OPTIMIZATION